Bedside gastrointestinal ultrasound combined with acute gastrointestinal injury score to guide enteral nutrition therapy in critically patients - Jiawei Lai; Shuhong Chen; Linli Chen; Daofeng Huang; Jinzhan Lin; Qingjiang Zheng (BMC Anesthesiology, 2022)
Abstract Background To use gastric ultrasound to evaluate function and to determine the start time of enteral nutrition (EN) in patients with acute gastrointestinal injury (AGI). Methods We reviewed records from 105 patients who suffered AGI levels two (AGI II). We recorded several data points, including ultrasonographic transverse area of gastric antrum (CSA), left descending colonic or right ascending colonic diameter (Diam), peristatic frequency (Peri), EN start time, EN dose, prealbumin (PA), and EN complications. The recovery of intestinal function after EN treatment was judged as success. If there was EN treatment complication, this was judged as failure. We analyzed the changes in gastrointestinal function after EN treatment, to determine feeding time. Results There were 69 patients in the successful group, and 36 in the failure group. There were no significant differences between the two groups in age, intra abdominal pressure (IAP), APACHE II, PA and disease composition (p > 0.05).There were significant differences in terms of EN startup time, CSA, Diam, Peri, and PA, between the EN success and failure groups. We found IAP does not reflect gastrointestinal function;CSA ≤ 9cm2, Diam ≤ 2.9 cm, Peri > 3 bpm, indicated that the three indexes could reflect the recovery of gastrointestinal function. Receiver operating curve analysis showed that combined CSA, Diam, Peri evaluation determined the best time to start EN. Conclusions Monitoring gastric antrum transversal area, colonic diameter, colonic peristatic frequency using ultrasound can guide the timing of initiation of enteral nutrition treatment.